174k views
2 votes
Select all expressions that represent a correct solution to the equation 6(x+4)=20. copied for free from openupresources.Org Select all that apply: A. (20−4)÷6 B. 16(20−4) C. 20−6−4 D. 20÷6−4 E. 1/6(20−24) F. (20−24)÷6

1 Answer

3 votes

Option D:
20 / 6-4 is the correct solution to the equation
6(x+4)=20

Option E:
(1)/(6) (20-24) is the correct solution to the equation
6(x+4)=20

Option F:
(20-24) / 6 is the correct solution to the equation
6(x+4)=20

Step-by-step explanation:

The expression is
6(x+4)=20

Let us find the value of x.


\begin{aligned}6(x+4) &=20 \\6 x+24 &=20 \\6 x &=-4 \\x &=-(2)/(3)\end{aligned}

Now, we shall find the expression that is equivalent to the value
x=-(2)/(3)

Option A:
(20-4) / 6

Simplifying the expression, we have,


(16)/(6)=(8)/(3)

Since,
(8)/(3) is not equivalent to
x=-(2)/(3), the expression
(20-4) / 6 is not equivalent to the equation
6(x+4)=20

Hence, Option A is not the correct answer.

Option B:
16(20-4)

Simplifying the expression, we have,


16(16)=256

Since, 256 is not equivalent to
x=-(2)/(3), the expression
16(20-4) is not equivalent to the equation
6(x+4)=20

Hence, Option B is not the correct answer.

Option C:
20-6-4

Simplifying the expression, we have,


20-10=10

Since, 10 is not equivalent to
x=-(2)/(3), the expression
20-6-4 is not equivalent to the equation
6(x+4)=20

Hence, Option C is not the correct answer.

Option D:
20 / 6-4

Using PEMDAS and simplifying the expression, we have,


$\begin{aligned}(20 / 6)-4 &=(10)/(3)-4 \\ &=(10-12)/(3) \\ &=-(2)/(3) \end{aligned}$

Thus,
-(2)/(3) is equivalent to
x=-(2)/(3), the expression
20 / 6-4 is equivalent to the equation
6(x+4)=20

Hence, Option D is the correct answer.

Option E:
(1)/(6) (20-24)

Simplifying the expression, we have,


$\begin{aligned} (1)/(6)(20-24) &=(1)/(6)(-4) \\ &=-(4)/(6) \\ &=-(2)/(3) \end{aligned}$

Thus,
-(2)/(3) is equivalent to
x=-(2)/(3), the expression
(1)/(6) (20-24) is equivalent to the equation
6(x+4)=20

Hence, Option E is the correct answer.

Option F:
(20-24) / 6

Simplifying the expression, we have,


$\begin{aligned}(20-24) / 6 &=-(4)/(6) \\ &=-(2)/(3) \end{aligned}$

Thus,
-(2)/(3) is equivalent to
x=-(2)/(3), the expression
(20-24) / 6 is equivalent to the equation
6(x+4)=20

Hence, Option F is the correct answer.

User Usman Farooq
by
5.9k points